Measurement of the social impact of nonprofit organizations in their specific community : design of a measurement methodology for Portugal - Andrade, Ana Catarina Gonçalves de Sousa (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research and CRM